Emergence of the State and local leadership in the Nile Valley (4th-3rd millennia BC) - Campagno, Marcelo Pedro (2021)
Studies on the emergence of the state tend to begin by focusing on communal dynamics, particularly their forms of leadership. They subsequently expand the scope of their research as the timeline continues on towards kingship and the political-administrative state apparatus. In this analytical strategy, communal spaces and their leaders are practically ignored once the analysis focuses on the state sphere and the figure of the king. Contrary to this approach, I will consider funerary, iconographic, and textual evidence of local leadership before and after the advent of the state in the Nile Valley between roughly the 4th and 3rd millennia BC. My objective is to understand how the nature of local leadership transforms as the state emerges and is consolidated on a global scale. Stan Hendrickx is indisputably a pillar in the field of studies on Predynastic and Early Dynastic Egypt, both for his own research and for that patient and enormous task of compiling all the existing bibliography on these issues. I am proud to have the opportunity to contribute to this book in his honour, with some reflections that begin with a topic that has been central to Stan's work: Predynastic leadership.